2011
DOI: 10.1099/jmm.0.030619-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of breakthrough contaminants associated with the conventional isolation of Mycobacterium tuberculosis

Abstract: Breakthrough contamination of tuberculosis (TB) cultures is a problem in that it allows the overgrowth of another bacterium present in the sputum specimen, which can potentially mask the presence of Mycobacterium tuberculosis. The aim of this study was to isolate and characterize the bacterial organisms responsible for such overgrowth and contamination, and to examine their susceptibility to (i) various chemical selective decontamination steps and (ii) antibiotics in liquid culture media, in an attempt to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 7 publications
3
24
2
Order By: Relevance
“…Similar observations were made by McClean et al [11], where they also observed that P. aeruginosa w as the predominant contaminant associated with the conventional isolation of Mycobacterium tuberculosis . That study also reported that 5% oxalic acid alone and in combination with NaOH was effective in eliminating P. aeruginosa [11]. The challenge in eliminating Aspergillus niger with the chemical agents used in the current study could be attributed to the fact that, most vegetative fungi and fungal spores are more resistant to decontamination agent.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar observations were made by McClean et al [11], where they also observed that P. aeruginosa w as the predominant contaminant associated with the conventional isolation of Mycobacterium tuberculosis . That study also reported that 5% oxalic acid alone and in combination with NaOH was effective in eliminating P. aeruginosa [11]. The challenge in eliminating Aspergillus niger with the chemical agents used in the current study could be attributed to the fact that, most vegetative fungi and fungal spores are more resistant to decontamination agent.…”
Section: Discussionsupporting
confidence: 88%
“…In spite of high activity recorded by some of the chemical agents, P. aeruginosa and A. niger proved to be the most challenging to inhibit among all the microbial isolates tested . This finding brings to the fore the intrinsic resistance properties exhibited by P. eruginosa to most antimicrobials [11]. Similar observations were made by McClean et al [11], where they also observed that P. aeruginosa w as the predominant contaminant associated with the conventional isolation of Mycobacterium tuberculosis .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…4 Another study also found that 2% NALC-NaOH more ease to be contaminated rather than the 4% NaOH method. 6,9 NALC is a good agent as mucolytic, but not as decontaminant, this factor could lead the capability of NALC-NaOH in recovery rate is weaker than Bleach NaOH NALC Bleach Oxalic bleach or NaOH and mask the growth of Mycobacterium tuberculosis. 2,6,10 Based on the number of contamination rate, 5% oxalic acid that had low number of positivity rate was also had a great number in contamination.…”
Section: Resultsmentioning
confidence: 99%